Virtual Control Desks for Nuclear Power Plants - Aghina, Maurício Alves C.; Mól, Antônio Carlos A.; Jorge, Carlos Alexandre F.; Santo, André C. do Espírito; Nomiya, Diogo V.; Cunha, Gerson G.; Landau, Luiz; Freitas, Victor Gonçalves G.; Lapa, Celso Marcelo F. (IntechOpen, 2011)
None